The Determinants of Economic Growth in the Central Sulawesi Region of Indonesia - Andi Herman Jaya; Patta Tope; Edhi Taqwa (Institut Bisnis dan Informatika Kesatuan, 2026)
Regional economic growth is an essential indicator of development performance that reflects the effectiveness of regional economic policies. This study examines the determinants of economic growth in Central Sulawesi Province across 13 municipalities and regencies during the period 2014–2024, focusing on population, labor force, investment, consumption per capita, and capital expenditure. The analysis employs a quantitative approach using panel data regression to assess both the joint and individual effects of these variables on regional economic growth. The empirical results indicate that, collectively, population, labor force, investment, consumption per capita, and capital expenditure significantly influence economic growth across the observed regions. In terms of individual effects, population and labor force are found to have negative and positive coefficients, respectively. However, both are statistically insignificant, indicating no meaningful direct impact on economic growth. Investment shows a positive and statistically significant effect, confirming its important role as a key driver of regional economic expansion. Conversely, consumption per capita has a statistically significant negative effect, suggesting that higher consumption levels are associated with lower economic growth in the region. Meanwhile, capital expenditure does not exhibit a statistically significant effect, implying that its current contribution to economic growth remains limited within the study period.